Low Bone Mineral Density in Middle-Aged Breast Cancer Survivors: Prevalence and Associated Factors - Conde, Délio Marques (S. Karger GmbH, 2012)
BACKGROUND: The aim of this study was to investigate the prevalence of low bone mineral density (BMD) and associated factors in middle-aged breast cancer survivors (BCS). PATIENTS AND METHODS: A cross-sectional study was conducted with 70 BCS of 45–65 years of age undergoing complete oncology treatment. Logistic regression models were used to identify factors associated with low BMD (osteopenia and osteoporosis taken together as a single group). RESULTS: The mean age of participants was 53.2 ± 5.9 years. BMD was low at the femoral neck in 28.6% of patients and at the lumbar spine in 45.7%. Body mass index ≤ 30 kg/m(2) (adjusted odds ratio (OR) 3.43; 95% confidence interval (CI) 1.0–11.3) and postmenopausal status (OR adjusted 20.42; 95% CI 2.0–201.2) were associated with low BMD at the lumbar spine. Femoral neck measurements, age > 50 years (OR 3.41; 95% CI 1.0–11.6), and time since diagnosis > 50 months (OR adjusted 3.34; 95% CI 1.0–11.3) increased the likelihood of low BMD. CONCLUSION: These findings show that low BMD is common in middle-aged BCS. Factors were identified that may affect BMD in BCS and should be considered when implementing strategies to minimize bone loss in middle-aged women with breast cancer.